Sensitivitas Black Garlic Terhadap Pertumbuhan Salmonella Sp. - Widhowati, Dyah; Mudji, Era Hari; Prakoso, Yos Adi; Aulia, Qoryza (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2022)
The aimed of this study to determine the sensitivity of Black garlic to the growth of Salmonella sp. with the disc paper test method (Kirby-bauer) as many as five treatments and five repetitions, P0- as a negative control using DMSO, P0+ as a positive control with chloramphenicol 30 μg. P1 as a treatment with a concentration of Black garlic of 80%, P2 as a treatment with a concentration of Black garlic of 90%, and P3 as a treatment with a concentration of Black garlic of 100%. Salmonella sp. inhibition zone results namely 00.0 mm at negative control, 10.28 mm at 80% concentration, 12.33 mm at 90% concentration, 14.56 mm at 100% concentration, and 29.00 mm at positive control. PIDG results were 0.00% in negative control, 71.40% at 80% concentration, 105.54% at 90% concentration, 142.68% at 100% concentration, and 383.42% in positive control. The data were obtained using One Way ANOVA which showed antibacterial sensitivity in Black garlic to Salmonella sp. with signification (P<0.05) so that it had a noticeable difference. The results of the disc paper test (Kirby-bauer) stated that Black garlic with a concentration of 100% has an active compound that is betterfor its activities in inhibiting the growth of Salmonella sp.